Batik Ciprat Langitan Sambung Roso as A Source of Local History Learning (Case Study at SMAN 1 Kawedanan Magetan) - Soebijantoro Soebijantoro; Khoirul Huda; Elaria Arda Sandi (PT Publikasiku Academic Solution, 2026)
Batik Ciprat Langitan Sambung Roso is a form of handicraft produced by persons with disabilities. This batik is distinguished by its unique production process and motifs rich in symbolic meaning. This study aims to: (1) describe the history of Batik Ciprat Langitan Sambung Roso in Simbatan Village; (2) examine the production process of Batik Ciprat Langitan Sambung Roso in Simbatan Village; and (3) identify the values embodied in Batik Ciprat Langitan that can be utilized as sources for history learning. The research employed a descriptive qualitative method. Data analysis was conducted using qualitative data analysis techniques that emphasize the quality and authenticity of data obtained from the research site. The analysis consisted of two stages, namely content analysis and interactive analysis. Content analysis was applied to document and archival data, while interactive analysis was used for interview and observation data through three analytical components: (a) data reduction, (b) data presentation, and (c) verification/conclusion. The findings indicate that Batik Ciprat Langitan Sambung Roso, which was established in 2015 with facilitation from the Ministry of Social Affairs, has continued to develop and demonstrates that persons with disabilities are able to fully participate and contribute to society. Batik Ciprat Langitan Sambung Roso, developed by artisans with disabilities in Simbatan Village, contains various values that are highly relevant as sources for history learning. These values include aesthetic, economic, social, cultural, and educational values. The values embodied in Batik Ciprat Langitan can be utilized as a source of local history learning for Grade X students at SMAN 1 Kawedanan.